Allonursing in river buffalo, Bubalus bubalis: Nepotism, incompetence, or thievery? - Murphey, Robert M.; Costa, Mateus J. R. Paranhos da[UNESP]; Silva, Roberto Gomes da [UNESP]; Souza, Roberto C. de [UNESP] (Academic Press (london) Ltd, 1995)
Allonursing was investigated in a dairy herd of 30 river buffalo cows and their calves. The primary behavioural variables were solicitations of allonursing by calves and acceptances of calves by cows. The sample of cows included a group of nine half-sisters, two additional pairs of half-sisters, and a pair of full-sisters. All of the calves were half-siblings owing to putative common paternity. Ancillary variables were age, milk-yield and docility of cows, as well as age, sex, weight and growth rate of calves. Three hundred and fifty-one instances of allonursing and 341 of filial nursing were recorded. There were large individual differences in the cows' tendencies to accept their own offspring and non-filial calves, and for the calves to successfully solicit milk from their mothers and other cows. Thirteen of the 30 cows accounted for 97% of the allonursing. Frequent allonursing was correlated with decreased growth rate in the donors' calves. Allonursing was unrelated to kinship or reciprocal relationships among the cows, and was associated with a lack of maternal experience in young cows and apparent milk theft by hungry calves whose mothers were not providing them with sufficient milk. © 1995 The Association for the Study of Animal Behaviour.
Keywords: Allonursing; River buffalo; Water buffalo; Bubalus bubalis